Insects in flight: direct visualization and flow measurements - Bomphrey, R (Institute of Physics Publishing, 2006)
The study of insect flight has been advanced in recent years by the advent and application of new quantitative flow diagnostic techniques, not least digital particle image velocimetry. More classical qualitative methods such as smoke flow visualization have also been applied with new goals for the rigorous description of flows around insects. The combination of techniques has led to the development of ideas which may be of some consequence to the designers of micro-air vehicles wishing to follow a biomimetic principle. Specifically, kinematic parameters such as wingbeat frequency and amplitude are discussed, along with some discussion of the investigation of morphological parameters such as wing design.